Carbonyl-rich covalent organic framework material as well as preparation method and application thereof
By preparing carbonyl-rich covalent organic framework materials, using hexazatriphenyl hexapropane and 2,7-diaminopyrene-4,5,9,10-tetraone as raw materials, the problem of few redox active sites and easy dissolution of the material in lithium-ion batteries was solved, and the effect of high specific capacity and excellent cycle stability was achieved.
Patent Information
- Application Number
- CN202411978116.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-03-28
AI Technical Summary
The existing covalent organic framework materials have problems such as few redox active sites, easy dissolution, resulting in low conductivity, low specific capacity and poor cycle stability in lithium-ion batteries.
Carbonyl-rich covalent organic frame material was prepared by using hexazatriphenyl trianhydride and 2,7-diaminopyrene-4,5,9,10-tetraone as raw materials to prepare a carbonyl-rich covalent organic framework material to form a material with high conductivity and abundant redox active sites.
The prepared carbonyl-rich covalent organic frame material exhibits high specific capacity and excellent cycling stability in lithium-ion batteries, solving the shortcomings of existing materials in terms of conductivity and cycling stability.
Smart Images

Figure CN119708482A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium batteries, and in particular relates to a carbonyl-rich covalent organic framework material and a preparation method and application thereof. Background Art
[0002] The energy shortage problem has promoted the development of the new energy industry. The rapid development of electric vehicles and electronic consumer products has promoted the development of high-energy-density energy storage systems. Lithium-ion batteries are considered to be the most promising energy storage devices of the next generation due to their high energy density, good cycle stability, and long service life. Compared with traditional lithium-ion batteries, aqueous lithium-ion batteries solve the problem of reduced conductivity and reduced cycle performance caused by the dissolution of organic negative electrode materials in organic electrolytes, and are safer to operate, lower cost, and more environmentally friendly.
[0003] Among many organic negative electrode materials, covalent organic frameworks (COFs) are widely used as electrode materials for lithium-ion batteries because of their long-range adjustable structure, rich porous structure, designable redox active groups and high chemical stability. Among them, covalent organic framework materials with C=O active sites have attracted widespread attention from scientists, mainly because of their high conductivity and rich redox active sites. C=O reacts with Li through coordination reaction. + Combined to form a coordination bond CO-Li, providing Li + The intercalation / deintercalation platform provides high cycle stability and high specific capacity for aqueous lithium-ion batteries.
[0004] Although there are many covalent organic framework materials reported so far, these materials still have problems such as few redox active sites, easy dissolution in electrolytes, resulting in low conductivity, low specific capacity, and poor cycle stability. In order to overcome the above shortcomings, many scientists have found that covalent organic framework materials (COFs) have adjustable structures and pores. The diversity of covalent bonds and organic building block connection methods also provides covalent organic framework materials (COFs) with diverse structures. A variety of redox reaction active sites can be designed through the selection of organic building blocks. However, due to the fact that covalent organic framework materials are easily soluble in electrolyte solutions, resulting in reduced conductivity and poor electrochemical performance, their application in lithium-ion batteries is limited. The desire to obtain covalent organic framework materials with high specific capacity and high cycle stability is still an urgent problem in this field. Summary of the invention
[0005] The purpose of the present invention is to provide a carbonyl-rich covalent organic framework material and a preparation method and application thereof. The carbonyl-rich covalent organic framework material is used as a negative electrode material for aqueous lithium-ion batteries, which exhibits higher specific capacity and cycle stability.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a carbonyl-rich covalent organic framework material, which is prepared from hexaazatrimellitic acid trianhydride and 2,7-diaminopyrene-4,5,9,10-tetraketone.
[0008] The second technical solution of the present invention is to provide a method for preparing the above-mentioned carbonyl-rich covalent organic framework material, comprising the following steps:
[0009] Hexaazatrimellitic acid trianhydride and 2,7-diaminopyrene-4,5,9,10-tetraone are dissolved in a solvent and heated for reaction to prepare a carbonyl-rich covalent organic framework material.
[0010] Preferably, the solvent is obtained by mixing N-methylpyrrolidone, mesitylene and isoquinoline.
[0011] The above solvent used in the present invention is a mixed solvent commonly used in the preparation of covalent organic framework materials in the art.
[0012] Preferably, the molar ratio of the azatrimellitic acid trianhydride to the 2,7-diaminopyrene-4,5,9,10-tetraketone is not less than 1:1.5.
[0013] More preferably, the molar ratio of the azatrimellitic acid trianhydride to the 2,7-diaminopyrene-4,5,9,10-tetraone is 1:1.5.
[0014] Preferably, the temperature of the heating reaction is not less than 180° C. and the time is not less than 120 hours.
[0015] Preferably, the heating reaction is carried out in a sealed environment.
[0016] Preferably, the heating reaction further comprises a step of removing oxygen and water vapor in the reaction system.
[0017] The method for removing oxygen and water vapor in the reaction system is to introduce nitrogen into the reaction system.
[0018] Preferably, the heating reaction further comprises the steps of centrifugation and washing.
[0019] Wherein, the washing liquid used for washing can be selected from DMF and acetone.
[0020] The third technical solution of the present invention is to provide an application of the above-mentioned carbonyl-rich covalent organic framework material in lithium-ion battery electrode materials.
[0021] Preferably, the lithium ion battery is an aqueous lithium ion battery.
[0022] The fourth technical solution of the present invention is to provide a negative electrode material for a lithium-ion battery, wherein the active material is the above-mentioned carbonyl-rich covalent organic framework material.
[0023] The fifth technical solution of the present invention: provides a method for preparing the above-mentioned lithium-ion battery negative electrode material, comprising the following steps: mixing the carbonyl-rich covalent organic framework material, a conductive agent, a binder and a solvent to prepare an electrode slurry, coating the electrode slurry on a current collector, and obtaining the lithium-ion battery negative electrode material after drying.
[0024] Optionally, the conductive agent is KS-6 and ECP; the binder is sodium carboxymethyl cellulose (CMC); the solvent is ethanol aqueous solution; and the current collector is copper foil.
[0025] The beneficial technical effects of the present invention are as follows:
[0026] The carbonyl-rich covalent organic framework material provided by the present invention has a novel and stable structure and is rich in carbonyl redox active sites and can be used as a raw material for electrode materials of lithium ion batteries.
[0027] The synthesis method provided by the invention has simple synthesis steps, low requirements on synthesis equipment and high yield.
[0028] The electrode material prepared by using the carbonyl-rich covalent organic framework material provided by the present invention as an active material has good conductivity, high specific capacity and strong cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the synthesis of HAT-COF in Example 1 of the present invention.
[0030] Figure 2 This is the XRD pattern of the HAT-COF prepared in Example 1 of the present invention.
[0031] Figure 3 The SEM images of the HAT-COF prepared in Example 1 of the present invention, wherein (a) to (f) are SEM images at different magnifications.
[0032] Figure 4 These are EDX element distribution images of the HAT-COF prepared in Example 1 of the present invention, wherein (a) is the distribution image of the C element, (b) is the distribution image of the N element, and (c) is the distribution image of the O element.
[0033] Figure 5 TEM images of HAT-COF prepared in Example 1 of the present invention, wherein (a) to (f) are TEM images at different magnifications.
[0034] Figure 6 These are the N2 adsorption-desorption and pore size distribution curves of the HAT-COF prepared in Example 1 of the present invention, wherein (a) is the N2 adsorption-desorption curve, and (b) is the pore size distribution curve.
[0035] Figure 7 This is the TGA curve of HAT-COF prepared in Example 1 of the present invention.
[0036] Figure 8 The first three charge and discharge curves (a) and rate performance curve (b) of the negative electrode sheet of a lithium-ion battery containing HAT-COF in Example 1 are shown.
[0037] Fig. 9 CV curve (a) and pseudocapacitance curve (b) of the negative electrode sheet of a lithium-ion battery containing the HAT-COF in Example 1.
[0038] Fig.10 This is the EIS spectrum of the negative electrode sheet of a lithium-ion battery containing the HAT-COF in Example 1. DETAILED DESCRIPTION
[0039] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.
[0040] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0041] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.
[0042] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0043] Unless otherwise specified, the "room temperature" in the embodiments of the present invention refers to a temperature of 20±10°C.
[0044] Example 1
[0045] Preparation of carbonyl-rich covalent organic framework materials:
[0046] In a 10mL reactor, add 1.0mmol of hexaazatrimellitic acid trianhydride, 1.5mmol of 2,7-diaminopyrene-4,5,9,10-tetraketone, 1.0mL of N-methylpyrrolidone, 1.0mL of mesitylene and 0.05mL of isoquinoline. Stir the mixture at room temperature for 10min, then introduce N2 into the resulting suspension and bubble for 5 minutes. After sealing it, heat it to 180℃ and react at a constant temperature for 120h. After cooling to room temperature, centrifuge the resulting precipitate, wash it three times with DMF and acetone respectively, and dry it in vacuum at 80℃ for 2 hours to obtain a black product, which is a carbonyl-rich covalent organic framework material (HAT-COF), with a yield of 76% (calculated based on 2,7-diaminopyrene-4,5,9,10-tetraketone).
[0047] Example 1 Schematic diagram of the synthesis of HAT-COF is shown in Figure 1 .
[0048] The HAT-COF prepared in Example 1 was characterized:
[0049] The XRD pattern of HAT-COF prepared in Example 1 is shown in Figure 2 The XRD results show that there is a sharp diffraction peak at 2θ=25°, indicating that HAT-COF is a porous carbon structure.
[0050] The SEM image of HAT-COF prepared in Example 1 is shown in Figure 3 , where (a) to (f) are SEM images at different magnifications.
[0051] The EDX element distribution image of HAT-COF prepared in Example 1 is shown in Figure 4 , where (a) is the distribution image of the C element, (b) is the distribution image of the N element, and (c) is the distribution image of the O element.
[0052] The TEM image of HAT-COF prepared in Example 1 is shown in Figure 5 , where (a) to (f) are TEM images at different magnifications.
[0053] SEM, TEM morphology analysis and EDX spectrum analysis show that the HAT-COF material prepared in the present invention is a rectangular block microporous structure, the internal structure is precisely combined, and the C, N, and O elements are evenly distributed on the skeleton.
[0054] The N2 adsorption and desorption and pore size distribution curves of the HAT-COF prepared in Example 1 are shown in Figure 6 , where (a) is the N2 adsorption-desorption curve, and (b) is the pore size distribution curve.
[0055] The N2 adsorption-desorption test and pore size distribution showed that the N2 adsorption-desorption curve was a type I isotherm, the pore size of HAT-COF was a mesoporous structure, and the pore size distribution was between 0-55 nm.
[0056] The thermogravimetric analysis (TGA) results of HAT-COF prepared in Example 1 are shown in Figure 7 .
[0057] The TGA curve shows that the weight decreases at 100°C, mainly due to the evaporation of water in the material. After 283°C, there is a significant weight loss, indicating that it has high thermal stability.
[0058] Example 2
[0059] Assembling CR2025 button cells using HAT-COF:
[0060] The HAT-COF, KS-6, ECP and CMC prepared in Example 1 were mixed in a mass ratio of 6:2:2:1, and then an ethanol aqueous solution (V 乙醇 :V 水 =5:95) as a solvent, grind evenly to obtain an electrode slurry; coat the obtained electrode slurry on a 12μm copper foil with a coating thickness of 50μm, and dry at 100°C for 12h to obtain a negative electrode sheet for a lithium ion battery; cut the obtained negative electrode sheet for a lithium ion battery into a circular sheet with a diameter of 12mm, and use a metal lithium sheet with a diameter of 15mm for the lithium ion battery counter electrode, and the electrolyte is a LiTFSI-dimethyl ether (DME)-1,3-dioxolane (DOL) lithium electrolyte (V DME :V DOL =1:1, LiTFSI concentration is 1M), and assembled into CR2025 button cells in a glove box filled with argon. The prepared CR2025 button cells were used to test the electrochemical performance of the HAT-COF prepared in Example 1.
[0061] The first three charge and discharge curves (a) and rate performance curves (b) of the lithium-ion battery negative electrode sheet containing HAT-COF in Example 1 are shown in Figure 8 . Figure 8 Display, at 100mA·g -1 At a current density of 2.5 200 mAh g / cm2, the first discharge capacity of the electrode material containing HAT-COF is 2559.233 mAh g / cm2. -1 The first charge capacity is 1839.670 mAh g -1 ; The rate performance tested at different current densities also shows that the HAT-COF electrode material has good electrochemical reversibility.
[0062] At room temperature, within the voltage range of 0.01 to 3.0 V (scan rate of 0.1 mv / s), a cyclic voltammetry test was performed on the negative electrode sheet of a lithium-ion battery containing the HAT-COF in Example 1. The CV curve (a) and pseudocapacitance curve (b) are shown in FIG. Fig. 9 . Fig. 9 It shows that a more obvious cathode peak appears at 0.22V, corresponding to Li + In the pseudocapacitance curve, as the scan rate increases, the obtained CV curves almost overlap, indicating that the electrode material containing HAT-COF has good redox reversibility and excellent cycle stability.
[0063] The electrochemical impedance spectroscopy (EIS) spectrum of the negative electrode sheet of the lithium-ion battery containing HAT-COF in Example 1 is shown in Fig.10 . Fig.10 The impedance spectrum is composed of a semicircle in the high-frequency region and a slash in the low-frequency region, which represent the charge transfer impedance (RCT) and Warburg impedance, respectively. The semicircle of the electrode material containing HAT-COF is smaller in the high-medium frequency region, indicating that it has a smaller impedance and better conductivity. The angle of the curve in the low-frequency region is also close to 45°, indicating that Li + The diffusion rate in the electrolyte is fast. And in the range of 0.01V to 3V, at 100mA·g -1 At a current density of 2.5 240 mAh g / cm2, the electrode material containing HAT-COF in the assembled aqueous lithium-ion battery provided 2559.233 mAh g / cm2. -1 The first discharge specific capacity is large, and it has excellent cycle stability.
[0064] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.
Claims
1. A carbonyl-rich covalent organic framework material, characterized in that: It is prepared from hexaazatrimellityl hexacarboxylic acid trianhydride and 2,7-diaminopyrene-4,5,9,10-tetraketone.
2. A method for preparing the carbonyl-rich covalent organic framework material according to claim 1, characterized in that: The following steps are involved: Hexaazatrimellitic acid trianhydride and 2,7-diaminopyrene-4,5,9,10-tetraone are dissolved in a solvent and heated for reaction to prepare a carbonyl-rich covalent organic framework material.
3. The preparation method according to claim 2, characterized in that: The solvent is obtained by mixing N-methylpyrrolidone, mesitylene and isoquinoline.
4. The preparation method according to claim 2, characterized in that: The molar ratio of the azatrimellitic acid trianhydride to the 2,7-diaminopyrene-4,5,9,10-tetraketone is not less than 1:1.
5.
5. The preparation method according to claim 2, characterized in that: The temperature of the heating reaction is not less than 180° C. and the time is not less than 120 hours.
6. The preparation method according to claim 2, characterized in that: The step of removing oxygen and water vapor in the reaction system is also included before the heating reaction.
7. The preparation method according to claim 2, characterized in that: The heating reaction further includes the steps of centrifugation and washing.
8. Use of the carbonyl-rich covalent organic framework material according to claim 1 in lithium-ion battery electrode materials.
9. A negative electrode material for a lithium ion battery, characterized in that: The active material is the carbonyl-rich covalent organic framework material according to claim 1.
10. A method for preparing the negative electrode material for a lithium ion battery according to claim 9, characterized in that: The following steps are involved: The carbonyl-rich covalent organic framework material, a conductive agent, a binder and a solvent are mixed to prepare an electrode slurry, the electrode slurry is coated on a current collector, and the negative electrode material of the lithium-ion battery is obtained after drying.